Instrumen Aktivitas Hedging Pada Pasar Modal Syariah - Arief Yuswanto Nugroho,; Sari Sukmawati, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
The purpose of this study is to identify the factors that impact hedging actions with foreign currency derivative instruments in non-financial businesses listed on the IDX between 2020 and 2022. The data utilized is secondary data obtained from the websites of the Indonesian Stock Exchange and OJK. In this study, the population consists of all firms listed on the Indonesian Stock Exchange that are in the 2020–2022 sharia capital market. Meanwhile, the sample for this study consists of 77 organizations with transaction exposure and comprehensive data for research.